Diseño de experiencia para fomentar el uso de la bicicleta como medio de transporte en la ciudad de Medellín (2019)
The project is based on the current environmental contamination situation in the city of Medellín, which has forced the institutions to adopt strategies, policies, preventive measures, among other alternatives that aim to reduce the use of the automobile as a means of transportation, inviting all the actors on the road to transport themselves more sustainably; for example, the peak and environmental plaque, which by means of informative elements and sanctions to the offenders of this measure, invite the citizen to desist from the private vehicle and resort to the use of public transport, or share the private vehicle with other passengers, or adopt the bicycle for transport or economic incentives and benefits from public and private companies to employees who are transported to work by bicycle. Despite these actions, the citizen of Medellín finds it difficult to adopt the bicycle for transport, due to factors independent of geodemographic factors, such as the lack of interconnection of the bicycle path, the lack of a luminaire for it, and the lack of signaling of the same; and especially the road insecurity that occurs in the intersections and intersections where cyclists, pedestrians and motorists come together, these being the points of greatest mortality and morbidity of cyclists in the city. For this reason, an urban system was designed to illuminate the cycle path, inform the cyclist of the traffic light status, reduce the speed of the cyclist and provide the cyclist with support for the foot when waiting. It consists of a support element to the foot, which has integrated lighting and in turn is visually supported from the technique of 3D painting on the bicycle, inviting the bicycle user through it to reduce their speed and then make use of the element